Effects of Maternal Knowledge and Attitudes on the Incidence of Pneumonia in Fully Immunized Toddlers - Mandagi, Ayik Mirayanti; Prayogi, Ahmad Yuda; Rahman, Vidia Nuria; Nisa, Nahdhiah Khoirun; Febriana, Melati Octavia; Parenti, Uyun Loveni (Preventia: The Indonesian Journal of Public Health, 2025)
In toddlers, pneumonia still a leading cause of illness and death. It may be affected by maternal and environmental factors, for instance maternal knowledge and attitude towards family members who smoke. This study examined the correlated of mothers’ knowledge and attitudes regarding family members’ smoking with pneumonia in toddlers who had received complete immunization. A cross-sectional design was applied in June 2023 at three community health centers in Banyuwangi Regency. The respondents were 71 mothers of children aged ≥9 months with a history of or currently experiencing pneumonia and who had completed basic immunizations. The chi-square test was applied to analyze the data. The result show that maternal knowledge regarding pneumonia cases in toddlers (OR = 0.25; 95% CI: 0.094–0.685), knowledge regarding pneumonia prevention (OR = 0.017; 95% CI: 0.003–0.088), knowledge regarding pneumococcal conjugate vaccine (PCV) immunization (OR = 0.018; 95% CI: 0.002–0.148), knowledge regarding the impact of smoking (OR = 0.047; 95% CI: 0.010–0.225), and attitude towards family members who smoke (OR = 2.841; 95% CI: 1.067–7.569) were significantly correlated with pneumonia in toddlers (p < 0.05). Gender and maternal attitude towards early detection of pneumonia were not significantly correlated with pneumonia (p = 0.445 and p = 0.230, respectively). Improving maternal knowledge about pneumonia and the risks of smoking, promoting smoke-free households, and encouraging timely preventive actions for children are crucial for guiding public health interventions and informing healthcare practices to reduce pneumonia incidence in toddlers.